Psychoanalysis and Repetition: Why Do We Keep Making the Same Mistakes? - Nasio, Juan-David (State University of New York Press, 2019)
In Psychoanalysis and Repetition, Juan-David Nasio, one of the leading contemporary Lacanian psychoanalysts in France, argues that unconcious repetition represents the core of psychoanalysis as well as no less than the fundamental constitution of the human being–back cover.
Keywords: Lacan; Jacques; 1901-1981; Psychoanalysis; Repetition (Philosophy); dept.phi; faculty_collection

Opportunity and responsibility for health - Cavallero, Eric (The Journal of Ethics, 2019)
Wealth and income are highly predictive of health and longevity. Egalitarians who maintain that this “socioeconomic-status gradient” in health is unjust are challenged by the fact that a significant component of it is owed to the higher prevalence of certain kinds of voluntary risk-taking among members of lower socioeconomic groups. Some egalitarians have argued that these apparently free personal choices are not genuinely free, and that those who make them should not be held morally responsible for the resulting harms to their health. I argue to the contrary that such choices usually are fully free, and that those who make them are responsible for their consequences. This does not imply, however, that society cannot also be responsible for those consequences. It is responsible for them if they are statistically foreseeable and avoidable outcomes of unjust public institutions and policies. I show that many of the harms to health that contribute to the voluntary behavioral component of the SES health gradient satisfy that description. Society can therefore be morally responsible for those harms, even though the individuals who suffer them are also fully responsible for them.
3 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/101-073-524-576-49X, pop00282 tex.type: [object Object]
Keywords: Equality of opportunity; Health; Personal responsibility; SES gradient in health; Social responsibility; dept.phi; peer-reviewed

How do we make sense of the thesis “bai (white) ma (horse) fei (is not) ma (horse)”? - Yang, Xiaomei (Dao, 2019)
In this article, I introduce a new interpretation of the puzzling thesis “bai 白 (white) ma 馬 (horse) fei 非 (is not) ma 馬 (horse)” argued by Gongsun Long 公孫龍 in his essay “On White Horse (Bai Ma Lun 白馬論).” I argue that previous interpretations, which can be grouped under the name of “attribute-object interpretations,” are not satisfactory, and that the thesis on the new interpretation is not about attributes or objects, but about names. My argument focuses on the disagreement over inseparability of white (shou bai zhi zheng 守白之爭) between Gongsun Long and his interlocutor in the text of “On White Horse.” On my interpretation or the name interpretation, the disagreement is about whether constituents of a syntactically complex or multi-term name are separable or have their contextually independent meanings. Gongsun Long’s thesis makes perfect sense on my interpretation, and is supported by the text and other preserved texts collected in GongsunLong Zi 公孫龍子. The name interpretation can also make sense of some puzzling expressions of sophists in the classic period.
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/045-736-172-501-878, pop00333
Keywords: Complex name; Descriptive phrase; Inseparability of white; Simple name; White Horse; dept.phi; peer-reviewed